PENGARUH PEMBERIAN EDUKASI AUDIOVISUAL TENTANG PERAWATAN PAYUDARA DENGAN KELANCARAN ASI PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS BALOI PERMAI KOTA BATAM TAHUN 2024 - Harlina, Talitha; Utami, Risqi; Ribut Sulistyawati, Tri (Universitas Batam, 2025)
Exclusive breastfeeding is a critical step in preparing a healthy generation from an early stage. This study highlights the importance of exclusive breastfeeding for infant growth and development, as well as reducing the risk of disease. Although the WHO and UNICEF recommend exclusive breastfeeding for the first six months of a baby's life, coverage in Indonesia has not yet met the established targets. Contributing factors to this low coverage include a lack of knowledge among mothers about breastfeeding and breast care. The purpose of this study is to evaluate the effectiveness of audiovisual education in improving postnatal mothers' knowledge about breast care and supporting the success of exclusive breastfeeding. The research method employed a quantitative approach with a pretest-posttest design on a group of postnatal mothers. An audiovisual educational intervention was provided, and knowledge about breast care and exclusive breastfeeding practices were measured before and after the intervention. The results showed a significant increase in mothers' knowledge about breast care from 40% to 80%, and exclusive breastfeeding coverage increased from 60% to 90% after the intervention. The Wilcoxon test indicated that this increase was significant with a sig (2-tailed) value of 0.000. In conclusion, audiovisual education is an effective method for improving postnatal mothers' knowledge about breast care and supporting the success of exclusive breastfeeding. This effort is expected to contribute to increased coverage of exclusive breastfeeding in Indonesia, supporting optimal infant growth and development, and reducing infant morbidity and mortality rates